Image of God as predictor of coping strategies - Jesyp, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
It has been clarified that the image of God predicts the choice of the strategy in overcoming difficulties in life. Believer's image of loving God is related to willingness actively influence  resolving  problems. By creating an image of indifferent God one shows that he/she is passive spectator in life, who expects problems to go away on their own. If one is not certain who God is for him/her then it gets much harder for them to choose copying-strategies.
Keywords: image of God; secular coping-strategies; religious coping-strategies; believers